Cantu syndrome and hypopituitarism: implications for endocrine monitoring. (12th November 2019) - Theis, Nicholas J; Calvert, Toby; McIntyre, Peter; Robertson, Stephen P; Wheeler, Benjamin J
Abstract : Summary: Cantu syndrome, or hypertrichotic osteochondrodysplasia, is a rare, autosomal dominant genetically heterogeneous disorder. It is characterized by hypertrichosis, cardiac and skeletal anomalies and distinctive coarse facial features. We report a case where slowed growth velocity at 13 years led to identification of multiple pituitary hormone deficiencies. This adds to other reports of pituitary abnormalities in this condition and supports inclusion of endocrine monitoring in the clinical surveillance of patients with Cantu syndrome. Learning points: Cantu syndrome is a rare genetic disorder caused by pathogenic variants in the ABCC9 and KCNJ8 genes, which result in gain of function of the SUR2 or Kir6.1 subunits of widely expressed KATP channels. The main manifestations of the syndrome are varied, but most commonly include hypertrichosis, macrosomia, macrocephaly, coarse 'acromegaloid' facies, and a range of cardiac defects. Anterior pituitary dysfunction may be implicated in this disorder, and we propose that routine screening should be included in the clinical and biochemical surveillance of patients with Cantu syndrome.